2022
DOI: 10.1186/s12992-022-00807-7
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional investigation of the mental health and wellbeing among individuals who have been negatively impacted by the COVID-19 international border closure in Australia

Abstract: Background The COVID-19 pandemic resulted in the Australian government implementing strict international border closures. However, research has not yet investigated the mental health status of individuals impacted negatively by these international border closures. Methods The present study was a cross-sectional online survey of 3968 adults who reported being negatively affected by the border closure during June and July 2021. Psychological distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…Furthermore, when compared to DASS in the published COVID-19 studies and especially in studies focused on migrant workers (23)(24)(25), healthcare workers (20) or the general population (19,21,26), the scores of the present study are dramatically higher, over 50% more severe in some cases. Along with research indicating that those negatively impacted by Australian international border closures were at an increased risk of elevated psychological distress (27), these scores combined provide additional evidence that travel restrictions have negative psychological consequences towards those directly impacted by them.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, when compared to DASS in the published COVID-19 studies and especially in studies focused on migrant workers (23)(24)(25), healthcare workers (20) or the general population (19,21,26), the scores of the present study are dramatically higher, over 50% more severe in some cases. Along with research indicating that those negatively impacted by Australian international border closures were at an increased risk of elevated psychological distress (27), these scores combined provide additional evidence that travel restrictions have negative psychological consequences towards those directly impacted by them.…”
Section: Discussionmentioning
confidence: 91%
“…For example, in March 2020, the South Australian government declared a public health emergency, which included measures such as closures of state borders and physical distancing requirements (eg, a 3-day lockdown in November 2020). Unsurprisingly, previous studies have found detrimental effects of COVID-19 on mental health in large, representative Australian cohorts [ 99 , 100 ], individuals who have been impacted by the adverse border closure effects of COVID-19 [ 101 ], and university students [ 102 , 103 ]. Thus, it is noteworthy that although the Be Well Plan did not directly target symptoms of depression or anxiety, almost half of the sample (46.7% for depression, 44.0% for anxiety) showed a reliable change in the respective outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…closures were at an increased risk of elevated psychological distress [27], these scores combined provide additional evidence that travel restrictions have negative psychological consequences towards those directly impacted by them. As direct social contact has been shown to be a protective factor for psychological distress [25], it may explain why our respondents had much higher scores compared to the other populations, as they were unable to be with friends or family, either directly because of travel restrictions or indirectly due to quarantine or lockdown.…”
Section: Plos Onementioning
confidence: 90%